2019
DOI: 10.1080/01419870.2019.1574508
|View full text |Cite
|
Sign up to set email alerts
|

Transitional justice and acceptance of cohabitation in Cyprus

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Specifically, our representative sample reveals clear age differences on levels of prejudice, trust, and readiness for cohabitation. These trends go in opposite directions when comparing the two Cypriot communities, which is also consistent with some recent research in Cyprus (Psaltis et al, 2019). As a matter of fact, older people have experienced cohabitation in Cyprus and younger ones have not; however, whether they would actually opt for renewed cohabitation largely depends on their adherence to the official master narratives of the conflict, the current dominant political orientation of the community, and past political socialization during the respondent’s formative years in early adulthood.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Specifically, our representative sample reveals clear age differences on levels of prejudice, trust, and readiness for cohabitation. These trends go in opposite directions when comparing the two Cypriot communities, which is also consistent with some recent research in Cyprus (Psaltis et al, 2019). As a matter of fact, older people have experienced cohabitation in Cyprus and younger ones have not; however, whether they would actually opt for renewed cohabitation largely depends on their adherence to the official master narratives of the conflict, the current dominant political orientation of the community, and past political socialization during the respondent’s formative years in early adulthood.…”
Section: Discussionsupporting
confidence: 91%
“…Two studies concluded that older Greek Cypriots mostly report extensive positive contact, but older Turkish Cypriots mostly report rare and fairly negative contact in mixed villages (Lytras & Psaltis, 2011; Psaltis, 2016). In a recent study, Psaltis, Loizides, LaPierre, and Stefanovic (2019) found that age correlated positively with acceptance of renewed cohabitation in the Greek Cypriot community; conversely, in the Turkish Cypriot community, a negative correlation was reported.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The school system as a transmitter of acceptable knowledge fails to present the facts from an objective point of view. Instead, teachers tent to produce and reproduce a more fictionalised version of history events presenting Greek Cypriots as the sole victimised community that is constantly under threat due to the violation of international law and human rights by the Turkish State (Spyrou, 2011;Philippou & Klerides, 2010;Psaltis et al, 2019). Unsurprisingly, primary and secondary education in the north also promotes a view that is ethnocentric and articulates a narrative portraying their communities as the victimised community.…”
Section: What Does the Future Hold? Educating For Peacementioning
confidence: 99%